A note on credit aggregates as targets or indicators of monetary policy - VACIAGO, G. (PSL Quarterly Review, 2013)
With increasing deregulation and financial innovation in many domestic banking systems, it has been suggested that the present emphasis on controlling the money stock is no longer appropriate. Instead, a broader definition of credit should be introduced and movements in credit aggregates should be controlled. The author argues that there is no direct transmission mechanism between a broad credit aggregate and changes in private and government debt, and that the authorities have limited ability to control such an aggregate. Therefore its choice as the main target for monetary policy would be inappropriate. JEL: E52